Freeze-drying modeling of vial using BEM - Ramšak, M.; Ravnik, J.; Zadravec, M.; Hriberšek, M.; Iljaž, J. (Engineering analysis with boundary elements, 2017)
The paper reports on development of Boundary Element Method (BEM) based numerical algorithm for the numerical simulation of the freeze drying process in a vial. In the paper the problems of freeze-drying modeling are covered in detail. The BEM based algorithm is developed for the axisymmetrical geometry case using the Subdomain BEM approach. A special feature of the algorithm is an implicit representation of the interface conditions at the sublimation front, which is a great advantage of the proposed numerical scheme. As a test case the freeze drying of skim milk in a vial is selected. The numerical results show a good agreement with reference data proving that the developed numerical model is appropriate, accurate and fast in simulating the primary and secondary drying stage. The numerical analysis also shows that the time step during the secondary drying stage can be increased by a factor 100, which reduces the computational time drastically.